Assessment of root canal anatomy of maxillary and mandibular canine teeth : a cone-beam computed tomography study = Evaluación de la anatomía del canal radicular de caninos maxilares y mandibulares : un estudio de tomografía computarizada de haz cónico - Okumuş, Özlem
To investigate the root canal anatomy of permanent maxillary and mandibular canines in a Turkish subpopulation using cone beam computed tomography (CBCT). Retrospective CBCT data of 300 patients admitted to our clinic between 2016 and 2018 were screened and evaluated. A total of 235 patients, 100 males and 135 females, aged 14-76 years (mean age 37.27±13.40) were included in this study. A total of 191 (44,8%) maxillary canine teeth and 235 (55,2%) mandibular canine teeth were examined. The number of roots and root canal morphology according to Vertucci's classification, the presence of accessory canals, and the position of the apical foramen of the root were analyzed. The effect of gender and age on the incidence of root canal morphology was also investigated. The majority of the teeth had a Type I canal configuration in both maxillary canines (100%) and mandibular canines (92,8%). In the mandibular canines the other canal patterns found were Type III (6,8%), and Type II (0,4%). Apical foramen was centrally positioned in the majority of the teeth, 70,2% and 66,8% in maxillary and mandibular canines, respectively. The occurrence of two roots in mandibular canines was 3,8% and the root canal separation was found 53,8% and 46,2% in the middle and cervical third of the root, respectively. No significant statistical difference was observed effect of gender and age on the incidence of the root canal morphology and the position of the apical foramen. Due to the diverse morphology and the potential presence of a second canal for canine teeth among the Turkish subpopulation, dentists should perform endodontic treatments with greater care. CBCT is an accurate tool for the morphological assessment of the root canals.